Tinggalan Arkeologi di Pura Subak Ulun Suwi Sidewaas, Bangli - Panji Semara, Ida Bagus Gd (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p29, 2018)
Arca is one of the relics of the classical period that has various forms and is the development of human thought in the field of art and culture. Thought can be seen in Pura Subak Ulun Suwi Sidewaas Bangli which until now still functioned with the statue which amounted to 14 pieces. Some of the problems in this study include the form, function and meaning of archaeological remains in Pura Subak Ulun Suwi Sidewaas Bangli. This study uses data collection methods consisting of several stages of observation, interviews, and literature study. The next stage is the stage of data analysis, this stage using qualitative analysis and iconography analysis. The theory used in this research is the functional theory and the theory of semiotics, which is expected to solve the problems in this research. Archeology in Pura Subak Ulun Suwi Sidewaas Bangli encompasses two statues of bhatari embodiment, four statues of bhatara, one lingga tribhaga, two lingga above lapel and stela and five fragments of the statue. These stalks are believed to be a means to invoke the welfare of the plants that are incomes for the people who depend on the plantations. The holy water obtained from the temple is not only used for self-use, but also used for the fertility of cattle and plants. The residue that is sanctioned by the community of temple penyungsung has meaning as a means of worship, the worship means in question is symbolic of the goddess god or his ancestor in an effort to get closer to his ancestors.